PEMEX : the ethanol decision - Corrales Estrada, Martha; Cort, Todd; Elias, Jaan (London : SAGE Publications Ltd, 2017)
In the early 2000s, the Federal government of Mexico enacted a series of laws promoting the use of alternative fuels in gasoline, beginning with ethanol from sugarcane. This meant that the national oil company PEMEX had to find ways to implement this policy. Nevertheless, in spite of efforts by various government agencies as well as PEMEX, by mid-2014 no ethanol had been incorporated into Mexicos gasoline supply.
Originally published: Estrada, M. C., Cort, T., & Elias, J. (2014). PEMEX: The ethanol decision. 102-14. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/pemex/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Petroleos Mexicanos -- Case studies; Petroleum industry and trade -- Mexico -- Case studies; Fuel switching -- Mexico -- Case studies; Mexico -- Politics and government -- Case studies; Mexico -- Economic policy -- Case studies